1206 Sphingosine 1-phosphate (S1P) regulation of vascular and immune systems: Mechanisms and therapeutic approaches. (14th December 2022) - Hla, Timothy
Abstract : Metabolism of cellular membranes forms lipid mediators that activate their cognate G protein- coupled receptors (GPCR) to regulate cellular responses. Our laboratory has contributed to this area by cloning of the human cyclooxygenase-2 (COX-2) that produces prostanoids as well as cloning and deorphaning of the first S1P receptor (S1PR1). This GPCR is now the target of small molecule drugs that are approved to treat many autoimmune diseases, including multiple sclerosis and ulcerative colitis. Recent clinical trials are testing if S1PR-targeted compounds are beneficial for systemic lupus erythematosus (SLE). Our recent studies on S1P have focused on S1P chaperones, which are defined as proteins that bind and present S1P to its GPCRs to direct specific signaling modes. Specifically, HDL-bound apolipoprotein M (ApoM) binds to S1P and regulates specific biological processes, such as maintenance of vascular endothelial cell (EC) barrier function, suppression of cytokine-induced inflammatory gene expression, EC survival and regulation of lymphopoiesis. HDL-bound S1P levels are decreased in SLE, sepsis, diabetes, aging and cardiovascular disease, and contributes to pathological processes by suppressing EC S1PR1 signaling. To develop a therapeutic strategy to enhance HDL-S1P/EC S1PR1 signaling axis that supports EC resilience, we engineered two recombinant fusion proteins – a soluble form (ApoM-Fc) and ApoA1-ApoM (A1M) that forms HDL-like nanoparticles. Recent work shows that A1M chaperones S1P as well as prostacyclin (PGI2), enhances EC barrier function and suppress inflammatory processes in vitro and in vivo . ApoM-bound S1P does not suppress lymphocyte egress suggesting that its large size prevents it from entering secondary lymphoid organs and acting as a functional antagonist to downregulate lymphocyte S1PR1. Studies on chaperone bound S1P action on ECs during pathological changes will be presented. These mechanistic studies have deepened our understanding of S1P biology thus allows rational design of new therapeutic approaches to not only tame the immune system but also enhance vascular endothelial functions. Supported by NIH grants R35HL135821 and R01EY031715.